Challenges and Roles of Official Statistics in the Covid-19 Pandemic - Firman Firman (Department of Mathematics, Hasanuddin University, 2020)
Official Statistics is a statistical activity carried out by the government relating to the collecting, processing and presenting of data in the government sector. During the Covid-19 pandemic, the government statistical activities underwent a change. Especially in the case of data collection in the field. Data collection by face to face directly begin to switch to online methods. With intertnet connection and technology information tools, activity related collecting data stiil done by online, especially to eradicate pandemic Covid-19. Official Statistics plays an important role through data produced associate with Covid-19 and with these data, the appropiate decision to accomplish pandemic Covid-19 can be made